Tracking cryptographic keys and encrypted data using position verification. Issue 1 (15th July 2020) - Galambos, Máté; Bacsárdi, László
Abstract : Position verification is an emerging field of quantum cryptography. Its goal is to verify whether a distant communicating party is telling the truth about where they are. However, the problem is usually formulated in a way that the position is the only credential of that party, which cannot guarantee uniqueness. In this study, the authors show how a practically secure position verification algorithm – assuming it exists – might be used to track (i.e. repeatedly verify the position) of some unique key or cipher text. To achieve this, they rely on pre‐prepared position verification data called trackers. They also propose three algorithms that implement their general tracking scheme and examine some questions related to their security. These implementations include shuffling trackers into valuable data and hiding their memory address through a random permutation; using CNOT operations to entangle valuable data and trackers; and using random qubit strings from which either trackers or secret keys can be produced at will. These methods may be used to track a diplomatic package or reveal the location of a malicious party during a denial of service attack.